Establishing and developing national lifelong guidance policy forums : a manual for policy-makers and stakeholders - (:unkn) unknown (Office for Official Publications of the European Communities, 2008)
"The Council resolution on strengthening policies, systems and practices in guidance throughout life in Europe invites Member States to create a suitable institutional environment and adequate systematic devices for converging strategies towards building national and regional lifelong guidance systems across sectors, with high levels of equity, efficiency and quality. Improved cross-sectoral and multiprofessional cooperation, increased dialogue and stronger partnerships among key players and stakeholders are considered remedies for making lifelong guidance become a reality in Europe. This manual supports Member States in strengthening structures for more effective guidance policy formulation and implementation. It identifies outstanding initiatives, good practices as well as gives insights into strategic choices and experimental approaches that Member States have taken while setting up national guidance forums. This publication is an ideal tool for policy- and decision-makers with responsibility for national and regional guidance policies, systems and practices in the education and employment sectors." (Hrsg., BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; I 2.2 Europa; Lebenslanges Lernen; Lernberatung; Berufsberatung; Berufswahl; Netzwerk; Europäische Union